Chapter 4 Post-Fukushima anti-nuclear movement - Bochorodycz, Beata (Taylor & Francis, 2023)
The chapter analyzes the cycle of the anti-nuclear movement that followed the Fukushima accident in March 2011. Employing functional typology, the chapter categorizes the movement's organizations into seven types (direct action, research and education, policy advocacy, aid, watchdog, legal, and other) and shows that the post-Fukushima wave of protests was much broader in scope and more diverse in terms of actors and organizational forms than often assumed. Tracing the origins of the post-Fukushima cycle, the analysis reveals three streams of protests that emerged soon after the Fukushima accident (Freeters, Old Guard, Ecologists), which later merged to form a coalition, Hangenren. The direct-action groups that constitute the most visible form of social protest, called by Oguma Eiji "the flower of the movement," exhibit characteristics of new social movements, although the chapter underlines the fact that the post-Fukushima anti-nuclear ecosystem included both the new groups formed after March 2011 and the old ones established before and after the Chernobyl accident.